Risk factor analysis for massive lymphatic ascites after laparoscopic retroperitonal lymphadenectomy in gynecologic cancers and treatment using intranodal lymphangiography with glue embolization - Kong, Tae-Wook (J Gynecol Oncol, 2016)
OBJECTIVE: To evaluate risk factors for massive lymphatic ascites after laparoscopic retroperitoneal lymphadenectomy in gynecologic cancer and the feasibility of treatments using intranodal lymphangiography (INLAG) with glue embolization. METHODS: A retrospective analysis of 234 patients with gynecologic cancer who received laparoscopic retroperitonal lymphadenectomy between April 2006 and November 2015 was done. In June 2014, INLAG with glue embolization was initiated to manage massive lymphatic ascites. All possible clinicopathologic factors related to massive lymphatic ascites were determined in the pre-INLAG group (n=163). Clinical courses between pre-INLAG group and post-INLAG group (n=71) were compared. RESULTS: In the pre-INLAG group (n=163), four patients (2.5%) developed massive lymphatic ascites postoperatively. Postoperative lymphatic ascites was associated with liver cirrhosis (three cirrhotic patients, p<0.001). In the post-INLAG group, one patient with massive lymphatic ascites had a congestive heart failure and first received INLAG with glue embolization. She had pelvic drain removed within 7 days after INLAG. The mean duration of pelvic drain and hospital stay decreased after the introduction of INLAG (13.2 days vs. 10.9 days, p=0.001; 15.2 days vs. 12.6 days, p=0.001). There was no evidence of recurrence after this procedure. CONCLUSION: Underlying medical conditions related to the reduced effective circulating volume, such as liver cirrhosis and heart failure, may be associated with massive lymphatic ascites after retroperitoneal lymphadenectomy. INLAG with glue embolization can be an alternative treatment options to treat leaking lymphatic channels in patients with massive lymphatic leakage.